Gamification in Plant Education for Children - Nagda, Mudra; Mehta, Parth; Lamba, Simranjeet; Kanani, Pratik (International Journal of Psychosocial Rehabilitation, 2020)
Gen Z are true digital natives and as opposed to millennials and prior, they have grown up with ready access to phone screens in a constantly ‘plugged in’ concrete jungle environment. This has led to a crippled relationship with plants and gardening activities, which were rampant in generations prior to them (millennials, boomers). Since this age group is often non confident of keeping their plant alive, they often lose interest in the process of gardening, which requires patience. Our goal was to address this issue using gamification as a positive persuasive design method. Our research paves a way to use Gamification User Types Hexad Scale (GUTHS) in designing for societal change that begins at the grassroots. Many other sensors and monitoring systems for plants exist in the industry, but they are used for crops and farmlands. They are not designed with the purpose to persuade and motivate, which are imperative when our end users are young adults who have little to no connection with nature. Our research is unique as it regards gamification as a useful tool to use to curb the early steps of climate change, in a generation that has high motivation and purpose but low ability and trigger to do so. By using Gamification User Types Hexad Scale to personalize game mechanics, we attempt to design technology that can build a connection between plants and young adults. Our research finds that the ‘Philanthropist’, ‘Free Spirit’ and ‘Achiever’ user types are the dominant user types in children in the planting context.